Palynological evidence of the geoecological belts dynamics from Eastern Cordillera of NW Argentina (23° S) during the Pre-Last Glacial Maximum - Torres, Gonzalo Román (2016)
This paper presents the first palynological record for the dynamics of geoecological belts of the Eastern Cordillera in northwestern Argentina prior to the Last Glacial Maximum (LGM). The study was carried out on a 5-m deep sedimentary core raised at Laguna Blanca (23°09’S, 65°12’W; 4,256 m a.s.l.), province of Jujuy. The geochronology was based on three14C dating by AMS method. Results show the sensitive response of the geoecological belts to temperature and effective moisture variations from ca. 29,000 to ca. 25,000 cal. years BP. The High Andean belt probably suffered an altitudinal descent forced by intense cold climate conditions ca. 29,000 cal. years BP, and may have reached a comparable distribution to the present one on 26,300 cal. years BP, favored by a milder climate. The Puna belt did not suffer great changes, since it remained with low representation in the pollen spectrum. High percentages of tree species from the Yungas ca. 29,000 cal. years BP are probably a response to the intensification of anabatic winds ascending the slope of the Sub-Andean Range towards the Eastern Cordillera. These results represent an important contribution to the paleoenvironmental discussion of the Late Pleistocene for the northwestern Argentina, where the available information on vegetation history is scarce.